The Important Role of Sex-Related Sox Family Genes in the Sex Reversal of the Chinese Soft-Shelled Turtle (Pelodiscus sinensis) - Yubin Wang; Xiangzhong Luo; Chunjuan Qu; Tao Xu; Guiwei Zou; Hongwei Liang (Biology, 2022)
The Chinese soft-shelled turtle Pelodiscus sinensis shows obvious sexual dimorphism. The economic and nutrition value of male individuals are significantly higher than those of female individuals. Pseudo-females which are base to all-male breeding have been obtained by estrogen induction, while the gene function and molecular mechanism of sex reversal remain unclear in P. sinensis. Here, comparative transcriptome analyses of female, male, and pseudo-female gonads were performed, and 14,430 genes differentially expressed were identified in the pairwise comparison of three groups. GO and KEGG analyses were performed on the differentially expressed genes (DEGs), which mainly concentrated on steroid hormone synthesis. Furthermore, the results of gonadal transcriptome analysis revealed that 10 sex-related sox genes were differentially expressed in males vs. female, male vs. pseudo-female, and female vs. pseudo-female. Through the differential expression analysis of these 10 sox genes in mature gonads, six sox genes related to sex reversal were further screened. The molecular mechanism of the six sox genes in the embryo were analyzed during sex reversal after E2 treatment. In mature gonads, some sox family genes, such as sox9sox12, and sox30 were highly expressed in the testis, while sox1, sox3, sox6, sox11, and sox17 were lowly expressed. In the male embryos, exogenous estrogen can activate the expression of sox3 and inhibit the expression of sox8, sox9, and sox11. In summary, sox3 may have a role in the process of sex reversal from male to pseudo-female, when sox8 and sox9 are inhibited. Sox family genes affect both female and male pathways in the process of sex reversal, which provides a new insight for the all-male breeding of the Chinese soft-shelled turtle.